Plate-shaped glass article and manufacture and application thereof
By realizing deep exchange and optimized composition of sodium ions in glass products, the problem of prone to cracking in the prior art is solved, and the performance of crack resistance and cluster drop strength is significantly improved.
Patent Information
- Application Number
- CN202411537946.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-05
- Filing Date
- 2020-08-04
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to effectively prevent crack propagation in chemically tempered glass products, especially when it hits sharp objects, the glass products are prone to rupture.
By using glass products composed of SiO2, Al2O3 and Li2O, deep exchange of sodium ions is achieved, the Crack Initiation Load (CIL) value of glass products is increased, and the compressive stress layer depth is optimized by controlling the thickness and composition of glass products. (DoL) and network forming body content.
It significantly improves the crack resistance and drop-collapse strength of glass products, and can maintain integrity under large drop-off heights and shocks of sharp particles.
Smart Images

Figure CN119390348A_ABST
Abstract
Description
[0001] This application is a divisional application of patent application 202010771734.5 filed on August 4, 2020, with the invention name “Plate-shaped glass products, their manufacture and application”. Technical Field
[0002] The present invention relates generally to sheet-shaped glass products, in particular chemically toughened or at least chemically toughenable glass products, their production and their use. In addition, the present invention also relates to a glass composition. Background Art
[0003] For example, in the patent family of US 2019 / 0016632 A1 with the granted US patent US 9,593,42 B2 as the same patent family, the patent family of US2018 / 0057401 A1 with the granted US patent US10,294,151 B2 as the same patent family, the patent family of US2018 / 0029932 A1 with the granted US patent US10,259,746 B2 as the same patent family, the patent family of US2017 / 0166478 A1 with the granted US patent US 9,908,811 B2 as the same patent family, and the patent family of US2016 / 0122240 with the granted US patent US10,239,784 B2 as the same patent family. Patent family of A1, patent family of US 2016 / 0122239A1 with granted US patent US10,150,698B2 as a patent family, patent family of US2017 / 0295657 A1 with granted US patent US10,271,442B2 as a patent family, patent family of US2010 / 0028607 A1 with granted US patent US 8,312,739 B2 as a patent family, patent family of US2013 / 0224492 A1 with granted US patent US 9,359,251B2 as a patent family, patent family of US2016 / 0023944 A1 with granted US patent US 9,718,727 B2 as a patent family Patent family of A1, US2012 / 0052271 A1 with granted US10,227,253B2 as a patent family Patent family of A1, US2015 / 0030840 A1 with granted US10,227,253B2 as a patent family, US2014 / 0345325 A1, US2016 / 0257605 A1 with granted US9,487,434 B2 as a patent family, 2015 / 0239776 A1 with granted US9,517,968B2 as a patent family, US2015 / 0259244 A1 with granted US9,567,254 B2 as a patent family, US2014 / 0345325 A1, US2016 / 0257605 A1 with granted US9,487,434 B2 as a patent family, B2 is a patent family of the same patent US2017 / 0036952 A1, with the authorized US patent US10,266,447B2 is a patent family of the same patent US2018 / 0002223A1, with the authorized US patent US 9,517,968 B2 as a patent family of US 2017 / 0129803A1, US 2016 / 0102014 A1 with issued US patent US10,266,447B2 as a patent family of US 2016 / 0102014 A1, US 9,676,663 B2 as a patent family of US 2015 / 0368153 A1 with issued US patent US 9,902,648B2 as a patent family of US 2015 / 0368148 A1, US 9,908,812B2, US 2016 / 0264452 A1 and issued US patent US 9,902,648 Patent family of B2, US2016 / 102011 A1 and granted US patent US 9,593,042 Patent family of B2, patent family of WO 2012 / 126394A1, patent family of US2014 / 0308526 A1 and granted US patent US 9,540,278B2, patent family of US2011 / 0294648 A1 and granted US patent US 8,759,238B2, patent family of US2010 / 0035038 A1 and granted US patent US 8,075,999 B2, patent family of US 4,055,703, patent family of DE 10 2010 009 584 A1 and granted German patent DE 102010 009 584B4 and patent family with granted US patent US10351471 Patent family of US patent application US 2016 / 0347655A1 with B2, patent family of CN 102690059 A and granted Chinese patent CN 102690059B, patent family of US2016 / 0356760 A1 and granted US patent US10,180,416B2, patent family of WO 2017 / 049028A1 with granted US patent US 9,897,574 B2 as a family patent, patent family of WO 2017 / 087742 A1, patent family of US2017 / 0291849 A1 and granted US patent US10,017,417B2, patent family of US2017 / 0022093 A1 and granted US patent US 9,701,569 B2's patent family, US2017300088(A1) and the granted US patent US 9,977,Known chemically toughened glasses and / or chemically toughened or chemically toughened glass products and / or methods for producing such products are described in the patent family of EP 470 B2, the patent family of EP 1 593 658 A1, the granted European patent EP 1 593 658 B1 and the US patent applications US2005 / 0250639 A1 and US2018 / 0022638 A1 and the granted US patent US10,183,887 B2. Chemically toughened glasses can be divided into so-called aluminosilicate glasses (also called AS glasses, aluminosilicate glasses or aluminosilicate glasses) which comprise, in particular, Al2O3 and SiO2 and alkali metal oxides other than lithium oxide Li2O as components, and lithium aluminosilicate glasses (also called LAS glasses, lithium aluminosilicate glasses or lithium aluminosilicate glasses) which further comprise Li2O as a component.
[0004] Patent family of US2019 / 0152838 A1, patent family of US2013 / 0122284 A1 and granted US patent US9,156,724 B2, patent family of US2015 / 0079400 A1 with granted US patent US 9,714,188 B2, patent family of US2015 / 0099124 A1 and granted US patent US 9,701,574 B2, patent family of WO2019 / 085422 A1, patent family of US2017 / 0197869 A1 and granted US patent US10,131,567 B2, patent family of US2015 / 0030840 A1 and granted US patent US10,227,253 B2, patent family of US2015 / 0140325 Other prior art documents can be found in A1 and the patent family of granted US Patent US10,125,044B2, US2015 / 0118497 A1 and the patent family of granted US Patent US 9,822,032B2, US2012 / 0135852 A1 and the patent family of granted US Patent US 8,796,165B2, US2015 / 0147575 A1 and the patent family of granted US Patent US10,000,410B2, and US2015 / 0376050 A1 and the patent family of granted US Patent US 9,783,451 B2.
[0005] Chemically toughened glass products should generally have as large a DoL (Depth of Compressive Stress Layer, also called compressive stress zone or compressive stress depth) as possible. This is advantageous because further crack propagation is prevented by the compressive stress in the compressive stress zone. The larger the DoL, the deeper a crack can penetrate into the volume of the glass product without further spontaneous crack propagation.
[0006] In this case, the prestressed glazing is constructed such that a compressive stress zone, which is usually constructed on both main surfaces of the plate-shaped glazing, is connected to a tensile stress zone, wherein the compressive stress zone is preferably constructed in a very similar and possibly even symmetrical or approximately symmetrical manner on both main surfaces of the plate-shaped glazing, in particular with respect to a mirror plane passing through the center of the glazing and extending parallel to the main surfaces of the glazing. As soon as the crack grows long enough to extend through the compressive stress zone into the tensile stress zone, i.e., when the length of the crack is greater than the thickness of the compressive stress zone, the glazing will break.
[0007] Therefore, in order to strengthen so-called protective glasses (also called covers or cover glasses), for example for mobile terminal devices, glass compositions are selected that allow deep ion exchange. For example, so-called LAS glasses are used, which allow deep ion exchange of lithium ions (from the glass) with sodium ions (from the exchange bath).
[0008] As an alternative or supplementary solution, one can try to reduce the stress intensity of the crack. Glass is generally a brittle material with high stress intensity at the crack tip. It has also been shown, as mentioned above, that LAS glass, which can be ion exchanged very deeply, happens to have a very high brittleness, which leads to very high stress intensity at the crack tip. This is disadvantageous.
[0009] The stress intensity at the crack tip cannot be measured directly. However, it is related to CIL, the "Crack Initiation Load". This "Crack Initiation Load" describes the load at which, when the Vickers hardness meter is pressed in, two radial cracks are generated in the material starting from the corner of the indentation. The higher the value, the fewer cracks are formed in the glass.
[0010] Cracks may generally occur, for example, during the production of the glass article due to processing and / or handling. Cracks may also occur when the glass article is used, for example, when it is used as a cover glass for a mobile terminal device (such as a tablet or a smartphone).
[0011] In addition to glass, other transparent materials, such as crystalline materials such as Al2O3 (corundum, but also often referred to as sapphire or sapphire glass when used as cover glass) or transparent plastics are often used as covers. For these materials, the above-mentioned relationship with crack propagation and "CIL" applies accordingly.
[0012] Impacts on hard, rough substrates, for example, are crucial with regard to crack formation. Of particular importance here is how brittle the material of the so-called "shield" is, that is to say how prone the material of the shield (e.g. glass and / or glass product) is to the formation and propagation of cracks caused by impacts.
[0013] Since the glass is tempered as a "shield" in the application, in this case, on the one hand, the properties of the glass matrix itself are crucial. On the other hand, the stresses introduced into the tempered glass product by ion exchange also play a role.
[0014] Known LAS glasses which are optimized for ion exchange, i.e. which enable particularly large exchange depths, have only low CIL values, which are usually below 1 N at a relative air humidity of 40%. The CIL of brittle materials, in particular glass, is determined by repeatedly and uniformly pressing a Vickers hardness tester into the surface of the brittle material under a stable, controlled ambient humidity. The ambient humidity here refers to the relative air humidity in the environment of the test sample, in this case a sample of the brittle material, for example a sample of a glass product. In the prior art, the CIL value is usually specified, the CIL being determined in a dry environment, for example under a nitrogen atmosphere.
[0015] To date, it has not been possible to optimally inhibit the propagation of cracks introduced into chemically toughened glass products, in particular chemically toughened glass products including so-called LAS glasses. Even if very large exchange depths are achieved, in the event of deep cracks, the glass or glass product can break regardless of the exact value of the prestress achieved. In other words, when a rough surface is impacted with relatively large sharp particles, the glass or glass product including such glasses with very large exchange depths can break very quickly and fail. In contrast, some glasses with a high CIL, which have only a small thickness of the compressive stress zone, can also fail when in contact with relatively small sharp particles, because the cracks can quickly penetrate into the tensile stress zone of the glass product. This refers to such glasses with poor exchangeability. In particular, boroaluminosilicate glasses cannot achieve a large exchange depth.
[0016] Therefore, there is a need for glass and / or glass products with optimized strength properties, in particular chemically toughened or chemically toughenable glass products or glasses that have or can achieve high strength when impacted with sharp objects. In addition, there is a need for a manufacturing method for such glass products or glasses. Summary of the invention
[0017] The first object of the present invention is to provide a glass product, preferably a chemically toughened or chemically toughened glass product, which at least reduces the disadvantages of the prior art. Other aspects relate to the manufacture and use of such glass products and a glass composition of a chemically toughened glass.
[0018] The objects of the invention are achieved by the subject matter of the independent claims. Specific preferred embodiments are described in the dependent claims.
[0019] Therefore, the present invention relates to a plate-shaped, chemically toughened or chemically toughenable glass product, comprising glass having a composition comprising SiO2, Al2O3 and Li2O, the glass product having at least one of the following features:
[0020] CIL is greater than 1 N, preferably greater than 1.2 N, particularly preferably greater than 2 N and very particularly preferably greater than 3 N, wherein the CIL is preferably determined in the untempered state, and / or
[0021] In case of a glass article having a thickness of at least 0.4 mm up to a maximum of 0.55 mm, the DoL is at least 90 μm, preferably at least 100 μm and / or for a glass article thickness of greater than 0.55 mm up to a maximum of 0.7 mm the DoL is at least 100 μm, preferably at least 115 μm and / or for a thickness of greater than 0.7 mm up to a maximum of 1 mm the DoL is at least 115 μm, preferably at least 130 μm and for a glass article thickness of greater than 1 mm and preferably not more than 3 mm, preferably a maximum of 2 mm the DoL is at least 130 μm, and / or
[0022] - a content of network formers of at least 82% by weight and / or a content of alkali metal oxides of up to 14% by weight, preferably up to 12% by weight,
[0023] Such that when using a sandpaper grit of 60, the tempered glass article preferably has a set drop strength of a drop height (given in cm) of at least 50 and preferably not more than 150, wherein the drop height is given as an average of 15 samples.
[0024] This solution of chemically toughenable or chemically toughened glass products has a series of advantages.
[0025] By providing that the glass article comprises a glass article having a composition comprising SiO2, Al2O3 and Li2O, the glass article is constructed in such a way that a large exchange depth for sodium is achieved, because the glass article comprises LAS glass or itself consists of LAS glass.
[0026] In the embodiments disclosed herein, in the current method of manufacturing a glass article disclosed herein, the maximum CIL of the glass article is at most 5N, preferably at most 6N, more preferably at most 7.5N.
[0027] The glass product has at least one of the following characteristics:
[0028] The CIL is greater than 1 N, preferably greater than 1.2 N, particularly preferably greater than 2 N and very particularly preferably greater than 3 N, wherein the CIL is preferably determined in the untempered state.
[0029] This is advantageous because, with this solution, the frosted glass is already a glass that has a certain resistance to crack propagation.
[0030] It has been shown that the CIL determination on a tempered glass product gives different values than the CIL determination on an untempered glass product, i.e. generally substantially higher values. The reason for this is that the ion exchange produces compressive stress zones on the surface of the glass product, which inhibit the propagation of cracks and thus the glass from breaking. As a result, the glass only breaks when certain load limits are exceeded, which are determined by the prestress and are therefore of course higher than for untempered glass products. However, it has been shown that the CIL determination on an untempered glass product already provides valuable information about the properties of the glass, such as the inhibition of crack propagation. In the untempered state, a glass or glass product with advantageous mechanical properties is already present when the CIL value is greater than 1 N. However, the CIL is preferably greater than 1.2 N, particularly preferably greater than 2 N and very particularly preferably even greater than 3 N.
[0031] Here, the CIL is determined according to the following measurement specifications:
[0032] In principle, the CIL of a glass is determined by repeatedly and evenly pressing a Vickers hardness tester into the glass surface. The glass surface of a float glass is used here.
[0033] The glass article to be tested is first stored in a test atmosphere (40% relative air humidity in the laboratory, uncontrolled room temperature) for at least 24 hours. Then, in the test atmosphere, i.e. at a relative air humidity of 40% in the sample environment, an indentation is introduced with the aid of a Vickers hardness tester. The indentation force is increased in stages. At least 10 indentations are performed at each force level. After the introduction of 10 indentations into the test atmosphere and a stabilization time of 15 minutes, the number of radial cracks generated at the corners of the Vickers indentation is recorded for each indentation at each force level.
[0034] The force was increased until 4 radial cracks were reliably formed at the corners of the Vickers indentation during each indentation. For each force level, the mean and standard deviation of the number of radial cracks formed for all relevant indentations were calculated. The upper (subscript "o", mean + deviation), lower (subscript "u", mean - deviation) and average (mean) crack numbers were combined into one data set for each indentation force. For all three data sets, the Boltzmann curves were plotted for The fitting is based on:
[0035]
[0036] Where: A2 = 4 and A1 = 0
[0037] It is found that at the inflection point of the curve for a crack number of 2:
[0038] CIL=x0±((x0-xo)+(xu-x0)) / 2.
[0039] In this context, it should be pointed out that, in contrast to the prior art, the CIL determination was carried out here at a relative atmospheric humidity of 40%. This is therefore particularly important, since the contact of the glass with moisture, i.e. with water, has a decisive influence on the strength. Glass corrosion is initiated at the crack tip of the crack, which leads to the breaking of bonds in the glass network. The higher the relative atmospheric humidity, the lower the CIL of the glass.
[0040] Alternatively or additionally, the glass article is constructed such that, in the case of a glass article thickness of at least 0.4 mm up to a maximum of 0.55 mm, the DoL of the glass article in the tempered state is at least 90 μm, preferably at least 100 μm and / or for a glass article thickness of greater than 0.55 mm up to a maximum of 0.7 mm, the DoL is at least 100 μm, preferably at least 115 μm and / or for a glass article thickness of greater than 0.7 mm up to a maximum of 1 mm, the DoL is at least 115 μm, preferably at least 130 μm and for a glass article thickness of greater than 1 mm and preferably not more than 3 mm, preferably a maximum of 2 mm, the DoL is at least 130 μm.
[0041] This is advantageous since, even with relatively large particles, the load cannot penetrate into the regions of the glass article which are under tensile stress.
[0042] Alternatively or additionally, the glass article is designed such that it has a content of network formers of at least 82% by weight and / or a content of alkali metal oxides of not more than 14% by weight, preferably not more than 12% by weight.
[0043] A network former content of at least 82% by weight of the glass or glass article can be advantageous, since this results in a glass network which is rigidly, ie brittlely, constructed so that it includes a glass network capable of storing introduced compressive stresses.
[0044] At the same time or alternatively, it may be advantageous to limit the alkali oxide content of the glass and / or glass product to a maximum of 14% by weight, preferably a maximum of 12% by weight. This is because it has been shown that the prestressability of the glass can surprisingly be adversely affected by too high a content of alkali oxides. This is surprising because it has been assumed so far that a high content of alkali is required because chemical toughening is achieved by exchange of alkalis. However, it is assumed that a high content of alkali oxides leads to a lower rigidity of the network as a whole. This is because the fewer oxygen separation sites the glass network contains, the more rigid it is. However, by adding alkali oxides to the network former, in particular to the SiO2 glass network, oxygen separation sites are generated. Therefore, a limited content of alkali oxides is advantageous, which preferably should not exceed 14% by weight, preferably should not exceed 12% by weight.
[0045] Such a glazing can be tempered such that, when using a sandpaper grit of 60, the tempered glazing has a set drop strength (measured in cm for the drop height) of preferably at least 50 and preferably up to 150, wherein the drop height is given by the average value of 15 samples.
[0046] The so-called set drop test is a very important test for mobile terminal devices. This test refers to the test of the load that may occur in the actual application of the glass product, for example. For this purpose, the glass product is installed in the form of the glass product installed in, for example, a subsequent mobile device (such as a smartphone). A model of the terminal device, such as a smartphone, is thus constructed, in which the glass product is used, for example as a display cover. In this case, the weight of the model corresponds to the weight of the actual terminal device to a large extent, and the installation of the glass product is also comparable to it, but without using corresponding components. Then the model is dropped downward with the glass product onto a surface, for example, including particles with a small radius of curvature. Therefore, this type of experiment is intended to simulate actual loads, such as when a smartphone falls on asphalt or concrete. It is well known that rough ground, that is, ground with sharp small stones or sand grains protruding from it, is crucial for the integrity of the protective glass for mobile terminal devices. When the described imitations with glass fall on a smooth surface (such as granite) or fall on a rough surface with sandpaper (such as granite with sandpaper), the falling heights of these imitations are significantly different. The drop height using a rough ground simulated by granite with sandpaper stuck on it was less than the drop height on a smooth ground.
[0047] In this case, the set drop experiment is preferably performed as follows:
[0048] The glass plate is fixed to the sample holder and dropped from a cumulative drop height onto a specified ground surface. Figure 3 The glassware used in the drop test has a length of 99 mm and a width of 59 mm, and is Figure 4 As shown, the replica is magnetically fixed in the sample holder. Here, the plastic sheet is first glued into a metal housing with the aid of double-sided adhesive tape, which has the shape and weight of a holder for a mobile terminal device (such as a smartphone). For example, a plastic sheet with a thickness of between 4.35 mm and 4.6 mm is suitable (see Figure 5 The bonding is preferably carried out with the aid of a double-sided adhesive tape having a thickness of about 100 μm. The adhesive is then bonded with the aid of a double-sided adhesive tape, preferably with a thickness of 295 μm, in particular with the product number 05338. The plate-shaped glass to be tested is adhered to the plastic plate with a double-sided adhesive tape of the brand, so that a distance of 350 μm to 450 μm is generated between the upper edge of the housing or the support and the upper edge of the glass. The glass is located above the housing frame, and no direct contact is allowed between the glass body and the aluminum housing. The "set" with a weight of 177.5 g obtained in this way (which simulates the installation of the glass in a mobile terminal device and is a "copy" of an actual mobile terminal device (here in particular a smartphone)) is then dropped with the glass side down in the vertical direction (therefore with a zero drop direction) at an initial speed onto a surface with the size of DIN A4, the so-called impact surface. Here, the impact surface is produced in the following way: sandpaper with the corresponding grain size, for example with a grain size of 60 (#60), is adhered to the substrate with the help of a double-sided adhesive tape, for example with a thickness of 100 μm. A transparent, double-sided Tesa (10 m / 15 mm) adhesive tape with the product number 05338 is used. In the present disclosure, the particle size is specified according to the standards of the European Federation of Abrasive Manufacturers Association (FEPA), for example, see DIN ISO 6344, in particular DIN ISO 6344-2:2000-04, Schleifmittel auf Unterlagen- -Teil 2: Best immunity der P 12bis P 220 (Coated abrasives - Grain size analysis - Part 2: Determination of the grain size distribution of coarse abrasive grains P 12 to P 220) (ISO 6344-2:1998).
[0049] The substrate must be strong and preferably made of aluminum or alternatively steel. The weight of the substrate is about 3 kg, in the description disclosed here, it is an aluminum substrate. The sandpaper must be completely equipped with adhesive tape and attached without bubbles. The impact surface can only be used for ten drop tests and must be replaced after the tenth drop test. The sample, i.e. the obtained set, is loaded into the test device and the set is aligned with the help of a 2D level (circular level) so that it lies horizontally, with the plate-shaped glass product pointing to the floor, i.e. in the direction of the impact surface (see Figure 6 ). The first drop height is 25 cm, then a drop from a height of 30 cm is performed. If there is still no breakage, the drop height is increased in increments of 10 cm until glass breakage occurs. The breakage height, breakage origin, and breakage appearance are recorded. 15 samples are tested and the average is taken.
[0050] It may be advantageous to fix the plate-shaped glass item on the plastic sheet so that in the event of a glass breakage, the plate-shaped glass item remains attached to the film so that it can be removed as easily as possible and the glass item can be inspected. For this purpose, it is advisable to arrange a self-adhesive film, such as a film used for packaging books, between the plastic sheet and the plate-shaped glass item in addition to the adhesive tape used. With the aid of this film, the broken plate-shaped glass item can then be removed.
[0051] In this disclosure, the following provisions apply:
[0052] An exchange bath is understood to be a molten salt, wherein the molten salt is used in an ion exchange process for glass or glass products. In the present disclosure, the terms exchange bath and ion exchange bath are used synonymously.
[0053] Typically, technically pure salts are used for the exchange bath. This means that, although, for example, only sodium nitrate is used as the starting material for the exchange bath, certain impurities are still included in the exchange bath. In this case, the exchange bath is a melt of a salt, i.e., for example, sodium nitrate, or a mixture of salts, i.e., for example, a mixture of sodium and potassium salts. In this case, the composition of the exchange bath is given in such a way that it relates to the nominal composition of the exchange bath, without taking into account any impurities that may be present. Therefore, in the present disclosure, if a 100% sodium nitrate melt is mentioned, this means that only sodium nitrate is used as raw material. However, the actual sodium nitrate content of the exchange bath may differ from this and usually also differs, because, in particular, industrial raw materials have a certain amount of impurities. However, this amount is usually less than 5% by weight, in particular less than 1% by weight, relative to the total weight of the exchange bath.
[0054] Accordingly, when using an exchange bath with a mixture of different salts, the nominal contents of these salts are given without taking into account the limited industrial impurities in the initial raw materials. That is, an exchange bath with 90% by weight of KNO3 and 10% by weight of NaNO3 can still have small amounts of impurities, but these impurities are determined by the raw materials and should generally be less than 5% by weight, in particular less than 1% by weight, relative to the total weight of the exchange bath.
[0055] Furthermore, the composition of the exchange bath may also change during the ion exchange process, since lithium ions in particular migrate from the glass or glass product into the exchange bath as a result of the ongoing ion exchange. However, unless expressly stated otherwise, changes in the composition of the exchange bath due to aging are also not taken into account in this context. Specifically, in the present disclosure, when the composition of the exchange bath is given, the nominal initial composition applies.
[0056] In the present disclosure, stress distribution refers to the application of mechanical stress in a glass article (e.g., a glass sheet) within the thickness of the glass article considered in the figures. In the present disclosure, if a compressive stress distribution is mentioned, it is meant here a certain part of the stress distribution in which the stress is positive, i.e., greater than zero. Tensile stress has a negative sign.
[0057] In the present disclosure, a complex compressive stress distribution refers to a compressive stress distribution in which the compressive stress generated in a corresponding article (eg, a glass article) consists of at least two sub-regions.
[0058] The compressive stress stored in the tempered glass article is generated as the integral of the compressive stress within the thickness of the glass article. In the present disclosure, this integral is referred to as the compressive stress integral.
[0059] The tensile stress stored in the tempered glass product is generated as the integral of the tensile stress within the thickness of the glass product. In the present disclosure, this integral is referred to as the tensile stress integral. Therefore, in the present disclosure, the terms stored tensile stress and tensile stress integral may also be used synonymously.
[0060] In the present disclosure, a plate-shaped glass product refers to a glass product in which the lateral dimension in one spatial direction is at least one order of magnitude smaller than the lateral dimensions in the other two spatial directions, wherein these spatial directions are given relative to a Cartesian coordinate system in which these spatial direction distributions extend perpendicular to each other and in which case the thickness is measured from one main surface to another along the normal direction of the largest or main surface.
[0061] The thickness is at least one order of magnitude smaller than the width and length of the glass article, so in this case, the width and length may be of the same order of magnitude. However, the length of the glass article may also be much greater than its width. Therefore, in the present disclosure, the sheet glass article may also include a glass ribbon.
[0062] In the present disclosure, glass refers to a material, and a glass product refers to a product made of and / or comprising a glass material. The glass product may consist of glass or mainly comprise glass material, ie, comprise at least 90 weight %.
[0063] In the present disclosure, chemical toughening refers to a process in which the glass article is immersed in a so-called exchange bath. In this case, an ion exchange takes place. In the present disclosure, potassium exchange refers to the migration of potassium ions from the exchange bath into the glass article, in particular into the surface of the glass article, i.e., for example, being embedded in the surface of the glass article, wherein at the same time smaller alkali ions, such as sodium, migrate from the glass article into the exchange bath. Sodium exchange, correspondingly, refers to the migration of sodium ions from the exchange bath into the surface of the glass article, while smaller ions, such as lithium ions, migrate from the glass article, in particular from the surface of the glass article into the exchange bath. As described above, compressive stress zones are generated in the surface region of the glass article by this ion exchange.
[0064] In the present disclosure, the maximum tensile stress refers to the tensile stress value in the middle of the glass article, ie, at a depth of half the thickness of the glass article.
[0065] Tensile stress is usually assigned a negative sign, while compressive stress is assigned a positive sign, since the directions of compressive and tensile forces are opposite. If the magnitude of tensile stress is mentioned in the present disclosure without mentioning the sign, it should be understood that this refers to the numerical value of the stress. This is related to the definition of the stress sign, which is exactly what the person skilled in the art, i.e. the developers of tempered protective glass, usually uses with respect to the stress sign. This definition is different from the conventional designation usually used, for example in physics, in which compressive stress is marked as negative and tensile stress is marked as positive. However, in the present disclosure, as mentioned above, the definition of stress usually used in the glass industry is used here.
[0066] For highly temperable glasses (only these can be used, for example, as cover glasses for mobile devices with different strength requirements), high compressive stress values (700 MPa to 1000 MPa) are usually achieved at a compressive stress depth of 40 μm to 200 μm. If not only ion exchange but also a combined exchange of, for example, potassium and sodium ions occurs, as is usually the case in LAS glasses, characteristic quantities CS and DoL for compressive stress are usually also given for the individual components or ions, i.e., for example, the compressive stress resulting from potassium exchange is "CS potassium" and the corresponding compressive stress depth is "potassium DoL" or potassium compressive stress depth.
[0067] If the compressive stress depth is given relative to the respective exchanged component or ion, this compressive stress depth is also referred to as the so-called “exchange depth.” In the present disclosure, the terms exchange depth, compressive stress depth and DoL are used as synonyms.
[0068] However, in this context, it is worth noting that the terms "potassium DoL" or "sodium DoL" are also commonly used. But potassium DoL here refers to an inherent assumed value. Sodium DoL and DoL are again identical, just as potassium CS and CS are identical. For example, the value obtained by extending the intersection of the compressive stress curve obtained by potassium exchange with the X-axis is called "potassium DoL" or "potassium exchange depth". Therefore, if "potassium DoL" is mentioned, it refers to the value to be determined or determined as described above in the present disclosure, but the value itself is assumed.
[0069] In the present disclosure, "sharp impact" refers to a load in which damage is caused by a small sharp object or a plurality of such small sharp objects. In other words, this is an impact with one or more sharp objects, i.e., for example, an impact with particles having a very small radius of curvature or particles in which the angle of the tip is less than 100°.
[0070] If the grit of sandpaper is mentioned in the present disclosure, it is preferably specified in accordance with DIN ISO 6344. The grit is based on the measurement unit mesh. The larger the grit, the smaller the abrasive particles. In the present disclosure, the terms "60 grit" and "#60" are used synonymously to designate the grit, for example, with respect to the so-called 60 grit. Of course, this applies correspondingly to other grits, for example 100 or 180 grit.
[0071] In the present disclosure, the term ion field strength according to Dietzel is used. This term is used in particular for oxide glass matrices, with it being understood that this value can vary depending on the coordination number of the ions involved.
[0072] The terms network modifier and network former are to be understood according to the theory of Zachariasen.
[0073] In this case, in the present disclosure, in particular the following substances are referred to as network formers: SiO2, Al2O3, B2O3, P2O5.
[0074] In particular, alkali metal oxides and alkaline earth metal oxides are referred to as network modifiers.
[0075] In particular, ZrO2 is referred to as a so-called intermediate oxide.
[0076] According to one embodiment of the glass product, the glass and / or the glass product comprises up to 3% by weight of P2O5, preferably up to 2% by weight of P2O5, particularly preferably up to 1.7% by weight of P2O5.
[0077] P2O5 is a glass component that forms a network and can improve the fusibility of the glass. However, during the manufacturing process, P2O5 may cause difficulties because the material of the melting device may be corroded. Therefore, the content of phosphate is preferably limited.
[0078] According to a further embodiment of the glass product, the glass and / or the glass product comprises up to 7% by weight of B2O3, preferably up to 5% by weight of B2O3, particularly preferably up to 4.5% by weight of B2O3.
[0079] B2O3 is also a network-forming glass component and can be advantageous, since the B2O3 content of the glass lowers the melting point and thus increases the solubility of the glass. However, it has been shown that too high a content of glass that can be ion-exchanged can have a negative effect on tempering. This is not fully understood, but the reason may be that the boron-containing glass network may relax more easily, i.e., the rigidity is reduced. Therefore, according to one embodiment, the B2O3 content of the glass or glass article is limited.
[0080] Moreover, the B2O3 content of the glass also increases the scratch resistance. Therefore, it has been assumed so far that a certain B2O3 content of a chemically toughened or at least toughenable glass article should increase the resistance of the glass article to sharp impact loads. However, this effect appears to be limited, so that the glass and / or glass article according to embodiments has a content of at most 7% by weight, particularly preferably at most 5% by weight, and very particularly preferably at most 4.5% by weight.
[0081] According to one embodiment of the glass article, the elastic modulus (E-Modul) of the glass or the glass article is greater than 75 MPa, preferably greater than 80 MPa.
[0082] The elastic modulus of a material describes the material's resistance to deformation due to mechanical load. It has been shown that good temperability of glass or glass products can be at least partially related to the elastic modulus. Thus, glass with a high elastic modulus appears to be easier to temper or exhibits more favorable mechanical properties in the tempered state than glass with a low elastic modulus. It should be noted here that the mechanical properties of glass or glass products cannot be considered absolutely, but must be considered application-oriented. In the present disclosure, in particular those mechanical properties that are achieved for loads with sharp objects, in particular so-called sharp impact loads, are considered to be favorable mechanical properties.
[0083] Presumably, the reason for this correlation may be that the elastic modulus can be a macroscopically measurable expression of the microstructure of the glass, i.e., the structure in the plane of the glass network. In this case, the rigid glass network can be manifested macroscopically in a relatively high elastic modulus, which, according to embodiments of the glass or glass article according to the present disclosure, is generally caused, for example, by a relatively high content of network formers and / or types of network formers, in particular by a relatively low B2O3 content of the glass and / or glass article and / or a relatively low alkali ion content of the glass and / or glass article.
[0084] However, it is not clear which is the particularly decisive factor for the formation of a rigid, inflexible network. For example, one factor that should lead to the formation of a dense network is the content of network formers, in particular the content of SiO2. According to one embodiment of the glass product and / or the glass, the glass and / or the glass product comprises at least 57% by weight of SiO2, preferably at least 59% by weight of SiO2, particularly preferably at least 61% by weight of SiO2. It has been shown that with such a minimum SiO2 content, advantageous mechanical strengths of the glass product can be achieved.
[0085] Even though very high SiO2 contents, which are as close as possible to the SiO2 of quartz glass, can be advantageous in terms of forming a rigid network with a high modulus of elasticity, the SiO2 content of the glass or glass article is preferably limited. On the one hand, this is because glasses with very high SiO2 contents no longer have good meltability. However, it has also been shown that very rigid bodies (such as pure quartz glass) are also very brittle. In other words, such bodies themselves primarily have a high mechanical strength, which can be reflected, for example, in a high modulus of elasticity. However, as soon as loads occur that already lead to crack formation, in this case abrupt crack propagation can occur.
[0086] According to an embodiment, the content of the glass and / or glass product should not be too high and is advantageously limited. The glass and / or glass product preferably comprises up to 69% by weight of SiO2, preferably up to 67% by weight of SiO2. This ensures still good meltability.
[0087] Another component of the glass or glass product is Al2O3. Al2O3 is a component that also serves as a network former and is a very hard material in pure form as crystalline Al2O3 (corundum). Thus, it has been shown that Al2O3 as a glass component can contribute to the formation of mechanically advantageous properties of tempered glass products. Therefore, according to an embodiment of the glass or glass product, the glass or glass product comprises at least 17% by weight of Al2O3.
[0088] It is known that the number of oxygen atom separation sites is reduced by adding Al2O3 to alkali metal silicate glasses. Although this may be advantageous for constructing a rigid, non-yielding network, it is critical for the solubility and chemical resistance of the resulting glass or glass product. Therefore, according to an embodiment of the glass or glass product, the amount of Al2O3 in the glass or glass product is limited. According to an embodiment of the glass and / or glass product, the glass or glass product comprises up to 25% by weight of Al2O3, preferably up to 21% by weight of Al2O3.
[0089] It has been shown that for the construction of a glass network that can be tempered as well as possible in alkali silicate glasses, the components and the network formers Al2O3 and SiO2 are interdependent. In order for the glass to be ion-exchangeable in principle, the glass must contain alkali ions. However, the content of alkali ions weakens the strength of the glass network because oxygen separation sites are generated. These oxygen separation sites can be reduced by adding Al2O3 as a component to the glass. According to one embodiment of the glass and / or glass product, the sum of the SiO2 and Al2O3 contents of the glass and / or glass product is between at least 75% by weight and at most 92% by weight, preferably at most 90% by weight. This minimum Al2O3 and SiO2 content of the glass and / or glass product is advantageous because a stable, rigid network is obtained in this way, which also has at least sufficient chemical resistance. However, the content of SiO2 and Al2O3 network formers in the glass and / or in the glass should not be too high, since otherwise the glass is no longer fusible or can no longer be melted economically, so that, depending on the embodiment of the glass or the glass product, the content of network formers SiO2 and Al2O3 is up to 92% by weight, preferably up to 90% by weight. Alternatively or additionally, the total content of network formers in the glass and / or in the glass product is preferably not more than 92% by weight, particularly preferably not more than 90% by weight.
[0090] Furthermore, it has been shown that the content of Li2O has a positive effect on the formation of well-tempered glass or glass products, even if Li2O itself does not participate as a component in the ion exchange. The inventors assume that the introduction of lithium ions into the glass network results in a particularly dense glass structure, since lithium ions are small ions with a large field strength. This can be advantageous, since a particularly dense glass network should provide less volume for deformation under mechanical action (e.g., in the case of ion exchange, the exchange of smaller ions for larger ions), thereby compensating for mechanical deformations. However, this would improve the prestressability, since the introduced stresses would be better stored in the glass network.
[0091] Therefore, according to one embodiment of the glass and / or the glass article, the glass and / or the glass article comprises at least 3% by weight of Li2O, preferably at least 3.5% by weight of Li2O.
[0092] However, the amount of Li2O should not be too high and is preferably limited. As is well known, Li2O as a component in glass also causes glass segregation and / or crystallization. According to an embodiment of the glass and / or glass article, the glass and / or glass article comprises up to 5.5% by weight of Li2O.
[0093] Na2O is a network modifier as an alkali metal oxide. It is advantageous for the glass and / or glass product to include Na2O, since in this case an ion exchange of sodium ions with potassium ions, in particular a so-called mixed exchange, can be achieved. As also described above, this can achieve a particularly advantageous solution for the glass product in terms of mechanical properties. According to one embodiment of the glass or glass product, the glass and / or glass product includes at least 0.8% by weight of Na2O.
[0094] However, too much Na2O is disadvantageous. The Na2O content in particular reduces the chemical resistance of the glass, in particular the acid resistance. Therefore, depending on the embodiment of the glass and / or glass product, the Na2O content is preferably limited. According to one embodiment, the glass or glass product preferably comprises up to 8% by weight of Na2O, preferably up to 7.5% by weight of Na2O, particularly preferably up to 7% by weight of Na2O.
[0095] The glass article preferably should not have too small a thickness. The thickness of the glass article also affects its mechanical stability. Therefore, according to one embodiment, the glass article has a thickness of at least 0.4 mm, preferably at least 0.5 mm.
[0096] It is also advantageous if the glass article does not have an excessive thickness. Since, unlike transparent plastics, for example, glass has a high density, if the glass article is too thick, a mobile terminal device equipped with such a glass article would become too large, for example. Therefore, according to one embodiment, the glass article has a thickness of at most 3 mm, preferably at most 2 mm, particularly preferably at most 1 mm. With such a glass article having a thickness within the above limits, a good compromise is achieved between good mechanical strength and low weight of the glass article.
[0097] The present disclosure also relates to a lithium aluminosilicate glass and a glass product, the glass product comprising the glass or substantially (i.e. at least 50% by weight) or mainly (i.e. at least 90% by weight) or completely consisting of the glass. The lithium aluminosilicate glass comprises the following components measured in weight %:
[0098] SiO2 57 to 69, preferably 59 to 69, particularly preferably 61 to 69, wherein the upper limit is preferably 67,
[0099] Al2O3 17 to 25, preferably 17 to 21,
[0100] Li2O 3 to 5.5, preferably 3.5 to 5.5,
[0101] Na2O 0.8 to 8, preferably 0.8 to 7.5, particularly preferably 0.8 to 7,
[0102] For the data expressed in % by weight, the sum of the Al2O3 and SiO2 contents is preferably between at least 75 and at most 92, preferably at most 90.
[0103] It has been shown that such glasses which contain components within the above-mentioned limits can be designed particularly advantageously in a temperable manner. In particular, low crack tip strengths can be achieved with such glasses. Furthermore, the glasses also have a high CIL, and this already in the untempered state.
[0104] The lithium aluminosilicate glass can be subjected to a tempering process, wherein:
[0105] The ion exchange is carried out at a temperature of between a minimum of 380° C. and a maximum of 440° C. for a duration of at least 2 hours, preferably at least 4 hours and a maximum of 24 hours, in an exchange bath comprising between at least 20% by weight and up to 100% by weight of a sodium salt, preferably sodium nitrate NaNO 3, wherein a potassium salt, in particular potassium nitrate, can optionally be added to the exchange bath, in particular in such a form that the sum of the contents of sodium and potassium salts amounts to 100% by weight.
[0106] And optionally a second ion exchange is carried out in an exchange bath comprising between 0 and 10 wt.-% sodium salt, preferably sodium nitrate NaNO3, relative to the total amount of salt, at a temperature of the exchange bath of at least 380° C. and at most 440° C., for a duration of at least one hour and at most 6 hours, wherein a potassium salt, particularly preferably potassium nitrate KNO3, is added to the exchange bath, in particular in such a form that the sum of the contents of sodium and potassium salts reaches 100 wt.-%.
[0107] Additionally, further ion exchange steps may be performed.
[0108] Therefore, the present disclosure also relates to a method for manufacturing a glass product, in particular a glass product according to an embodiment of the present disclosure, the method comprising the steps of:
[0109] The ion exchange is carried out at a temperature between a minimum of 380° C. and a maximum of 440° C., for a duration of at least 2 hours, preferably at least 4 hours, and at most 24 hours, in an exchange bath comprising between at least 20% by weight and at most 100% by weight of a sodium salt, preferably sodium nitrate NaNO, wherein a potassium salt, in particular potassium nitrate, can optionally be added to the exchange bath, in particular in such a manner that the sum of the contents of sodium and potassium salts amounts to 100% by weight,
[0110] and optionally carrying out a second ion exchange in an exchange bath comprising between 0 and 10 wt.-% sodium salt, preferably sodium nitrate NaNO3, relative to the total amount of salts, at a temperature of the exchange bath of at least 380° C. and at most 440° C., for a duration of at least one hour and at most 6 hours, wherein a potassium salt, particularly preferably potassium nitrate KNO3, is added to the exchange bath, in particular in such a form that the sum of the contents of sodium and potassium salts amounts to 100 wt.-%,
[0111] and optionally including one or more further ion exchange steps.
[0112] The present disclosure also relates to a glass product, which is manufactured or can be manufactured by a method according to an embodiment of the present disclosure and / or the glass product includes the lithium aluminosilicate glass according to the present disclosure or is substantially, mainly or completely composed of such glass.
[0113] The glass product according to the present disclosure can be used as a cover panel, especially as a cover panel in an entertainment electronic device, especially for a display device, a screen of a computing device, a measuring device, a television device, especially as a cover panel for a mobile device, especially for at least one device selected from the following group, the group comprising: a mobile terminal, a mobile digital processing device, especially a mobile phone, a mobile computer, a PDA, a laptop computer, a tablet computer, a wearable device, a portable watch and a timing device, or as a protective glass window, especially as a protective glass window for a machine, or as a glass window in a high-speed train, or as safety glass, or as a car glass window, or in a diving watch, or in a submarine, or as a cover panel for explosion-proof equipment, especially for those explosion-proof equipment that stipulates that glass must be used.
[0114] According to an embodiment of the present disclosure, an exemplary composition range of the lithium aluminosilicate glass includes the following components measured in weight %:
[0115] SiO2 57 to 69, preferably 59 to 69, particularly preferably 61 to 69, wherein the upper limit is preferably 67,
[0116] Al2O3 17 to 25, preferably 17 to 21,
[0117] B2O3 0 to 7, preferably 0 to 5, particularly preferably 0 to 4.5,
[0118] Li2O 3 to 5.5, preferably 3.5 to 5.5,
[0119] Na2O 0.8 to 8, preferably 0.8 to 7.5, particularly preferably 0.8 to 7,
[0120] K2O 0 to 1, preferably 0 to 0.8, particularly preferably 0 to 0.7,
[0121] MgO 0 to 2, preferably 0 to 1.5, particularly preferably 0 to 1,
[0122] CaO 0 to 4.5,
[0123] SrO 0 to 2, preferably 0 to 1.5, particularly preferably 0 to 1,
[0124] ZnO 0 to 3, preferably 0 to 2, particularly preferably 0 to 1.5,
[0125] P2O5 0 to 3, preferably 0 to 2, particularly preferably 0 to 1.7,
[0126] ZrO2 0 to 3, preferably 0 to 2.8,
[0127] It may further include impurities and / or refining agents and / or coloring components in an amount not exceeding 2% by weight.
[0128] An exemplary composition of glass used to produce a plate-shaped glass article according to one embodiment may be given by the following components measured in % by weight:
[0129] SiO2 57 to 69, preferably 59 to 69, particularly preferably 61 to 69, wherein the upper limit is preferably 67,
[0130] Al2O3 17 to 25, preferably 17 to 21,
[0131] B2O3 0 to 7, preferably 0 to 5, particularly preferably 0 to 4.5,
[0132] Li2O 3 to 5.5, preferably 3.5 to 5.5,
[0133] Na2O 0.8 to 8, preferably 0.8 to 7.5, particularly preferably 0.8 to 7,
[0134] For the data expressed in % by weight, the sum of the Al2O3 and SiO2 contents is preferably between at least 75 and at most 92, preferably at most 90. BRIEF DESCRIPTION OF THE DRAWINGS
[0135] Figure 1 It is a schematic diagram not drawn to scale of a plate-shaped glass product according to an embodiment disclosed herein.
[0136] Figure 2 It is a cross-sectional schematic diagram not drawn to scale of a glass product 1 according to an embodiment disclosed herein.
[0137] Figure 3 An overall diagram of the set drop test structure is shown with individual component names.
[0138] Figure 4 The sample holding portion and trigger mechanism of the drop test structure are shown.
[0139] Figure 5 An aluminum housing and a plastic plate are shown as sample holder and sample replica.
[0140] Figure 6 Alignment of the sample replicas with the aid of a 2D level is shown. DETAILED DESCRIPTION
[0141] exist Figure 2 In the embodiment, the glass article 1 has two regions 101 arranged on two main surfaces of the glass article, which are under compressive stress and are also referred to as compressive stress regions. These compressive stress regions 101 also have Figure 2 The dimension "DoL" is schematically depicted in FIG. The DoL of a sheet-like glazing 1 may differ on both sides by an amount where these differences are generally within the range of measurement accuracy, and thus the DoL of a sheet-like glazing 1 is generally the same on both sides (at least within the range of measurement accuracy).
[0142] The tensile stress region 102 is located between the compressive stress regions 101 .
[0143] Reference numerals list
[0144] 1. Plate-shaped glass products;
[0145] 101 compressive stress area;
[0146] 102 The internal region of the glass article that is under tensile stress.
Claims
1. A plate-shaped, chemically toughened or chemically toughenable glass product, the glass product comprising glass, the glass having a composition comprising SiO2, Al2O3 and Li2O, the glass product having at least one of the following characteristics: - a CIL greater than 1 N, preferably greater than 1.2 N, particularly preferably greater than 2 N and very particularly preferably greater than 3 N, wherein the CIL is preferably determined in the untempered state, and / or - in case the glass article has a thickness of at least 0.4 mm up to a maximum of 0.55 mm, the DoL is at least 90 μm, preferably at least 100 μm and / or for a thickness of the glass article of greater than 0.55 mm up to a maximum of 0.7 mm, the DoL is at least 100 μm, preferably at least 115 μm and / or for a thickness of greater than 0.7 mm up to a maximum of 1 mm, the DoL is at least 115 μm, preferably at least 130 μm and for a thickness of the glass article of greater than 1 mm and preferably not exceeding 3 mm, preferably a maximum of 2 mm, the DoL is at least 130 μm, and / or - a content of network formers of at least 82% by weight and / or a content of alkali metal oxides of up to 14% by weight, preferably up to 12% by weight, Such that, preferably when using a sandpaper grit of 60, the tempered glass article has a set drop strength of at least 50 and preferably not more than 150 given as a drop height in cm, wherein the drop height is given as an average of 15 samples.
2. The glass product according to claim 1, wherein the glass and / or the glass product comprises a maximum of 3% by weight of P2O5, preferably a maximum of 2% by weight of P2O5, particularly preferably a maximum of 1.7% by weight of P2O5.
3. The glass product according to any one of claims 1 or 2, wherein the glass and / or the glass product comprises up to 7% by weight of B2O3, preferably up to 5% by weight of B2O3, particularly preferably up to 4.5% by weight of B2O3.
4. The glass article according to any one of claims 1 to 3, wherein the elastic modulus of the glass and / or the glass article is greater than 75 MPa, preferably greater than 80 MPa.
5. The glass product according to any one of claims 1 to 4, wherein the glass and / or the glass product comprises at least 57% by weight of SiO2, preferably at least 59% by weight of SiO2, particularly preferably at least 61% by weight of SiO2 and / or wherein the glass and / or the glass product comprises at most 69% by weight of SiO2, preferably at most 67% by weight of SiO2.
6. The glass article according to any one of claims 1 to 5, wherein the glass and / or the glass article comprises at least 17 wt.-% Al2O3 and / or wherein the glass and / or the glass article comprises up to 25 wt.-% Al2O3, preferably up to 21 wt.-% Al2O3.
7. The glass product according to any one of claims 1 to 6, wherein the sum of the Al2O3 and SiO2 contents of the glass and / or the glass product is between at least 75% by weight and at most 92% by weight, preferably at most 90% by weight, and / or wherein the total content of network formers in the glass and / or the glass product is not more than 92% by weight, particularly preferably not more than 90% by weight.
8. The glass article according to any one of claims 1 to 7, wherein the glass and / or the glass article comprises at least 3 wt.-% Li2O, preferably at least 3.5 wt.-% Li2O and / or wherein the glass and / or the glass article comprises at most 5.5 wt.-% Li2O.
9. The glass article according to any one of claims 1 to 8, wherein the glass and / or the glass article comprises at least 0.8 wt.-% Na2O and / or wherein the glass and / or the glass article comprises up to 8 wt.-% Na2O, preferably up to 7.5 wt.-% Na2O, particularly preferably up to 7 wt.-% Na2O.
10. The glass article according to any one of claims 1 to 9, wherein the glass article has a thickness of at least 0.4 mm, preferably at least 0.5 mm.
11. The glass article according to any one of claims 1 to 10, wherein the glass article has a thickness of not more than 3 mm, preferably not more than 2 mm, particularly preferably not more than 1 mm.
12. A lithium aluminosilicate glass comprising the following components measured in weight %: SiO2 57 to 69, preferably 59 to 69, particularly preferably 61 to 69, wherein the upper limit is preferably 67, Al2O3 17 to 25, preferably 17 to 21, Li2O 3 to 5.5, preferably 3.5 to 5.5, Na2O 0.8 to 8, preferably 0.8 to 7.5, particularly preferably 0.8 to 7, For the data expressed in % by weight, the sum of the Al2O3 and SiO2 contents is preferably between at least 75 and at most 92, preferably at most 90.
13. A method for producing a glass product, in particular according to any one of claims 1 to 11, comprising the steps of: - the ion exchange is carried out in an exchange bath comprising between at least 20% by weight and at most 100% by weight of a sodium salt, preferably sodium nitrate NaNO3, at a temperature between at least 380° C. and at most 440° C. for a duration of at least 2 hours, preferably at least 4 hours and at most 24 hours, wherein a potassium salt, in particular potassium nitrate, can optionally be added to the exchange bath, in particular in such a manner that the sum of the contents of sodium and potassium salts amounts to 100% by weight, and optionally carrying out a second ion exchange in an exchange bath comprising between 0 and 10 wt.-% sodium salt, preferably sodium nitrate NaNO3, relative to the total amount of salts, at a temperature of the exchange bath of at least 380° C. and at most 440° C., for a duration of at least one hour and at most 6 hours, wherein a potassium salt, particularly preferably potassium nitrate KNO3, is added to the exchange bath, in particular in such a manner that the sum of the contents of sodium and potassium salts amounts to 100 wt.-%, - and optionally comprising one or more further ion exchange steps.
14. A glass product manufactured or manufacturable by the method according to claim 13 and / or comprising the glass according to claim 12.
15. Use of the glass product according to any one of claims 1 to 11 and 14, the glass product is used as a cover panel, in particular as a cover panel in an apparatus for entertainment electronics, in particular for a display device, a screen of a computing device, a measuring device, a television device, in particular as a cover panel for a mobile device, in particular for at least one device selected from the following group, the group comprising: Mobile terminals, mobile digital processing devices, in particular mobile phones, mobile computers, PDAs, laptops, tablet computers, wearable devices, portable watches and timing devices, or as protective glass windows, in particular as protective glass windows for machines, or as glass windows in high-speed trains, or as safety glass, or as car glass windows, or in diving watches, or in submarines, or as covering panels for explosion-proof equipment, in particular for those explosion-proof equipment for which the use of glass is mandatory.
Citation Information
Patent Citations
Aluminosilicate glass for chemical tempering and glass ceramics
CN102690059A
Aluminosilicate glass and glass ceramics for chemical tempering
CN102690059B
Chemically tempered glass, methods for its manufacture and its use
DE102010009584A1
Chemically tempered glass, methods for its manufacture and its use
DE102010009584B4
Chemically and thermally pre-stressable lithium aluminosilicate float glass of high temperature resistance
EP1593658A1